Evaluating the duration of message transactions in broadcast wired/wireless fieldbus networks - Alves, Mário (2014)
Determining the response time of message transactions is one of the major concerns in the design of any distributed computer-controlled system. Such response time is mainly dependent on the medium access delay, the message length and the transmission delay. While the medium access delay in fieldbus networks has been thoroughly studied in the last few years, the transmission delay has been almost ignored as it is considered that it can be neglected when compared to the length of the message itself. Nevertheless, this assumption is no longer valid when considering the case of hybrid wired/wireless fieldbus networks, where the transmission delay through a series of different mediums can be several orders of magnitude longer than the length of the message itself. In this paper, we show how to compute the duration of message transactions in hybrid wired/wireless fieldbus networks. This duration is mainly dependent on the duration of the request and response frames and on the number and type of physical mediums that the frames must cross between initiator and responder. A case study of a hybrid wired/wireless fieldbus network is also presented, where it becomes clear the interest of the proposed approach